Socio‐economic, demographic, and clinical correlates of poor glycaemic control within insulin regimens among children with Type 1 diabetes: the SEARCH for Diabetes in Youth Study. Issue 8 (4th July 2019) - Snyder, L. L.; Stafford, J. M.; Dabelea, D.; Divers, J.; Imperatore, G.; Law, J.; Lawrence, J. M.; Pihoker, C.; Mayer‐Davis, E. J.
Abstract: Aim: To examine the distribution and association of sociodemographic, adherence, and barriers‐to‐care factors in relation to glycaemic control within insulin regimens in US children with Type 1 diabetes in the SEARCH for Diabetes in Youth Study. Methods: Self‐ or parent‐reported data from 1095 children with Type 1 diabetes aged 10–17 years were collected on insulin regimen, sociodemographics, diabetes self‐management, diabetes‐related family conflict and barriers to care. Multivariable logistic regression analysis identified poor glycaemic control correlates within each insulin regimen. Results: Participants included 694 children on insulin pump therapy, 188 receiving basal–bolus injections, and 213 on a mixed insulin regimen. Of these, 28.5%, 45.2% and 51.2%, respectively, had poor glycaemic control [HbA1c ≥ 80 mmol/mol (9.5%)]. Family conflict between parent and child regarding diabetes management was the only factor significantly associated with poor glycaemic control in all insulin regimens (insulin pump, P ≤ 0.0001; basal–bolus injections, P =0.0002; mixed insulin regimen, P =0.0103). For children on insulin pump, poor control was significantly associated with non‐white race ( P =0.0008), living in multiple households ( P =0.0331), having Medicaid insurance ( P =0.0090), and decreased insulin adherence ( P <0.0001). For children on a mixed insulin regimen, living in multiple households ( P =0.0256) and not spending enough time with healthcare provider ( P =0.0058) correlated with poor control. Conclusions: A high percentage of US children with Type 1 diabetes had poor glycaemic control, especially those not using an insulin pump. Early identification of children with risk factors associated with poor glycaemic control within insulin regimens and addressing diabetes‐related family conflict may allow interventions to improve diabetes management. What's new?: Despite advances in the treatment of Type 1 diabetes, a significant proportion of children with Type 1 diabetes have poor glycaemic control. This study of children with Type 1 diabetes identified multiple sociodemographic, adherence and barriers‐to‐care correlates of poor glycaemic control, which varied within each insulin regimen group. This study provides the largest Type 1 diabetes cohort examination of diabetes‐related family conflict, and found that family conflict regarding diabetes management was the only significant poor glycaemic correlate in all insulin regimens. Routine screening for and addressing of poor glycaemic correlates, including diabetes‐related family conflict, is critical in improving the care of children with Type 1 diabetes.